Medium‐chain fatty acids inhibit mitochondrial metabolism in astrocytes promoting astrocyte‐neuron lactate and ketone body shuttle systems. Issue 5 (2nd February 2016) - Thevenet, Jonathan; De Marchi, Umberto; Domingo, Jaime Santo; Christinat, Nicolas; Bultot, Laurent; Lefebvre, Gregory; Sakamoto, Kei; Descombes, Patrick; Masoodi, Mojgan; Wiederkehr, Andreas
Abstract : Medium‐chain triglycerides have been used as part of a ketogenic diet effective in reducing epileptic episodes. The health benefits of the derived medium‐chain fatty acids (MCFAs) are thought to result from the stimulation of liver ketogenesis providing fuel for the brain. We tested whether MCFAs have direct effects on energy metabolism in induced pluripotent stem cell‐derived human astrocytes and neurons. Using single‐cell imaging, we observed an acute pronounced reduction of the mitochondrial electrical potential and a concomitant drop of the NAD(P)H signal in astrocytes, but not in neurons. Despite the observed effects on mitochondrial function, MCFAs did not lower intracellular ATP levels or activate the energy sensor AMP‐activated protein kinase. ATP concentrations in astrocytes were unaltered, even when blocking the respiratory chain, suggesting compensation through accelerated glycolysis. The MCFA decanoic acid (300 μM) promoted glycolysis and augmented lactate formation by 49.6%. The shorter fatty acid octanoic acid (300 μM) did not affect glycolysis but increased the rates of astrocyte ketogenesis 2.17‐fold compared with that of control cells. MCFAs may have brain health benefits through the modulation of astrocyte metabolism leading to activation of shuttle systems that provide fuel to neighboring neurons in the form of lactate and ketone bodies.—Thevenet, J., De Marchi, U., Santo Domingo, J., Christinat, N., Bultot, L., Lefebvre, G., Sakamoto, K., Descombes, P., Masoodi, M., Wiederkehr, A. Medium‐chain fatty acids inhibit mitochondrial metabolism in astrocytes promoting astrocyte‐neuron lactate and ketone body shuttle systems. FASEB J. 30, 1913–1926 (2016). www.fasebj.org